Flora Malesiana, Series I. Volume 17 part 1. C. C. Berg, E. J. H. Corner y &F.M. Jarrett. / Flora Malesiana, Series I. Volume 17 part 2. C. C. Berg & E. J. H. Corner y . - Weiblen, G. D.; Clement, W. L. (Edinburgh Journal of Botany, 2007)
..